Information Models of the Television System - N. V. Lysenko; A. M. Monchak (Известия высших учебных заведений России: Радиоэлектроника, 2016)
Primary and secondary information model of the object, information about which is transmitted to the user and conversioned by them are reviewed. Formal description of information models is presented. For a simple mutually-orthogonal conversion the correct detection probability of image of the object represented by the secondary information model are defined.